Evaluation of clinical, radiological characteristics, and treatment outcomes of pediatric pseudotumor cerebri syndrome cases (Annals of Medical Research, 2025)
Aim: This study aims to evaluate the clinical, radiological, and treatment outcomes of pediatric patients diagnosed with Pseudotumor Cerebri Syndrome.Materials and Methods: This retrospective study included 21 children diagnosed with definite or possible Pseudotumor Cerebri Syndrome according to the revised Friedman diagnostic criteria, out of 115 patients evaluated between 2017 and 2019 at a pediatric neurology clinic. Clinical findings, radiological features, treatment responses, and prognosis were analyzed.Results:  The study cohort was predominantly female (85.7%), with a mean age of 12.8 years. The most common presenting symptoms were headache, visual disturbances, and vomiting. A key diagnostic finding was elevated cerebrospinal fluid (CSF) opening pressure (>280 mmH₂O), observed in 67% of patients. Two-thirds of the cases (66.6%) were classified as Primary Pseudotumor Cerebri Syndrome, while the remaining third (33.4%) were secondary, most frequently attributed to drug exposure or vitamin imbalances. The majority of patients showed significant clinical improvement following medical treatment with high-dose acetazolamide. Only a few required adjunctive therapies such as topiramate or corticosteroids, and recurrence was documented in only a single case. Additionally, MRI findings supportive of the diagnosis were present in a subset of patients.Conclusion: Early diagnosis and treatment of Pseudotumor Cerebri Syndrome in children can prevent permanent visual complications. A multidisciplinary approach, including ophthalmology and pediatric neurology, is essential for accurate diagnosis, effective treatment, and favorable outcomes.
Keywords: Pseudotumor cerebri syndrome; Pediatric neurology; Increased intracranial pressure; Acetazolamide treatment; Papilledema